Del Diálogo Oriente-Occidente a la Alianza de Civilizaciones - Bueno, Rafael (Huarte de San Juan. Geografía e Historia, 2006)
The East West Dialogue is not a new process. People from the East and the West have been interacting, dealing, fighting and coexisting in harmony and peacefully during centuries. After all those years of contacts, where relations were sometimes insignificant, sometimes intense, the current situation seems to indicate that in both, the East and the West remain the great ignorance of the other, not by lack of interest in many cases nor by lack of the means. At the same time, the flows of contacts and mainly the superiority of a side, the West on East has marked significantly this peculiar relation. Due to this perception, in July of 2004, Casa Asia it decided to organize, within the frame of the Universal Fórum of the Cultures Barcelona 2004, a East West Dialogue that served to try to shorten the distances that separate us and to work and to deepen on what it unites to us. A year after this first encounter of Casa Asia in Barcelona, the president of the Spanish government, Jose Luis Rodriguez Zapatero, pronounced its speech in the General debate of 59º period of sessions of the General Assembly of the United Nations in which launched a call in favour of an Alliance of Civilizations. The objective of this initiative has as mission “to wake up the world-wide conscience on the risks of which a wall could rises due to the lack of understanding between the West and the Arab and Islamic world and that well known and fearing” clash of civilizations could happen. Consequently, from Casa Asia, we thought that both initiatives were not necessary but complementary. Asia has much to say to the present global situation and from the West we have not only means but also the moral obligation to make that their voice is listened to and understood.